2015
DOI: 10.1016/j.jpainsymman.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled, Randomized Trial of Octreotide in Malignant Bowel Obstruction

Abstract: Although there was no reduction in the number of days free of vomiting, the multivariate analysis suggests that further study of somatostatin analogues in this setting is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 31 publications
1
95
0
1
Order By: Relevance
“…Our work provides data about the combination and generates hypothesis to be confirmed. Of note, median time to desobstruction in our study was 5 days, which is consistent with reported experiences with a single antisecretory agent [4,[15][16][17]. The last desobstruction occurred at day 20 of admission, showing that rate of resolution is initially quick but progressively slows down, as shown in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our work provides data about the combination and generates hypothesis to be confirmed. Of note, median time to desobstruction in our study was 5 days, which is consistent with reported experiences with a single antisecretory agent [4,[15][16][17]. The last desobstruction occurred at day 20 of admission, showing that rate of resolution is initially quick but progressively slows down, as shown in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…A recent randomised trial failed to show benefit of octreotide given first line in addition to standard therapy (which included dexamethasone) on the primary outcome of vomit-free days. 35 However, there was a reduction in the number of vomiting episodes in patients receiving octreotide. The role of octreotide as second line therapy in patients who continue to vomit despite standard first line therapy requires further research.…”
Section: Antisecretory Agentsmentioning
confidence: 97%
“…An adjusted multivariable regression showed over a 50% reduction in vomiting attributable to octreotide but with twice the incidence of colicky pain requiring treatment. And octreotide costs at least $15 for each 100 mcg dose, typically given 3 times a day, which puts it out of reach of hospice.The authors concluded that more study was needed 85 .…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%